Rhetoric and realities of London 2012 Olympic education and participation 'legacies': voices from the core and periphery. Issue 8 (16th November 2016) - Kohe, Geoffery Z.; Bowen-Jones, Will
Abstract : A legacy emphasis was one of the fundamental pillars of the London 2012 Olympic Games. The notion of an Olympic legacy was predicated on assumptions that the event's value would not purely derive from the sporting spectacle, but rather from the 'success' of enduring effects met out in London and across the country. For physical education students and practitioners, Olympic legacy agendas translated into persistent pressure to increase inspiration, engagement, participation and performance in the subject, sport and physical activity. Responding to this context, and cognizant of significant disciplinary scholarship, this paper reports initial data from the first phase of a longitudinal study involving Key Stage Three (students aged 11–13) cohorts in two comparable United Kingdom schools: the first an inner-city (core) London school adjacent to the Olympic Park in Stratford, East London ( n = 150); the second a (peripheral) school in the Midlands ( n = 198). The research involved the use of themed questionnaires focusing on self-reported attitudes towards the Olympic Games and experiences of physical education, sport and physical activity. Students from both schools demonstrated a wide variety of attitudes towards physical education and sport; yet, minor variances emerged regarding extreme enthusiasm levels. Both cohorts also expressed considerably mixed feelings towards the impending Olympic Games. Strong and variable responses were also reported regarding inspiration levels, ticketing acquisition and engagement levels. Consequently, this investigation can be read within the broader context of legacy debates and aligns well with physical educationalists' ongoing discomfort regarding legacy imperatives being enforced upon the discipline and its practitioners. Our work reiterates a shared disciplinary scepticism that while an Olympic Games may temporarily affect young peoples' affectations for sport (and maybe physical education and physical activity), it may not provide the best, or most appropriate, mechanism for sustained attitudinal and/or social changes en masse .